Спектроскопічний та термічний аналіз кристалічного поліморфізму орто-бензилфенолу - Baran, J.; Davydova, N. A.; Drozd, M.; Ponezha, E. A.; Reznichenko, V. Ya. (Publishing house "Academperiodika", 2018)
In situ, we present the experimental spectroscopic proof of the existence of polymorphism in ortho-benzylphenol. Infrared spectroscopy was used for the first time to investigate the structural changes during the crystallization of a metastable phase, which is transformed, in the course of time, into a stable one. The results show that, in the stable and metastable phases, different conformers of ortho-benzylphenol molecule predominate, which differ in the orientation of the aromatic rings relative to the connecting methylene bridge. Namely, it is shown that the transformation of the metastable phase into a stable one is accompanied by the rotation of the OH-substituted aromatic ring relative to the connecting methylene bridge from 59.9∘ to 180.0∘ in the molecule of ortho-benzylphenol. The DSC experiment has shown that the process of nucleation of a metastable phase preferentially develops below ∼1.1 Tg (243 K), the crystallization occurs at ∼272 K, and the melting happens at 290.2 K. The difference in the temperature regions of nucleation and crystallization explains a good glass-forming status of ortho-benzylphenol.